Palynological analysis of the late Ordovician - early Silurian black shales in South China provides new insights for the investigation of pore systems in shale gas reservoirs. (June 2020) - Tan, Jingqiang; Hu, Ruining; Wang, Wenhui; Dick, Jeffrey
Abstract: The late Ordovician Wufeng and early Silurian Lungmachi formations are primary targets for shale gas exploration in the southeastern marginal area of the Sichuan Basin, Southwest China. In this research, different groups of micro-fossils (large numbers of taxonomically unrelated organic- and inorganic-walled fossil groups) from the two formations were analyzed in order to investigate their pore characters under the evaluation of shale gas reservoirs. A large number of biological autologous micro-nano pores in radiolarians, sponge spicules, acritarchs, conodonts, chitinozoans, and scolecodonts were analyzed. The results show that most pores are densely and randomly distributed with honeycomb or irregular shapes. Although the samples are over mature and were deeply buried, micro-fossils remain in a large number of biological micro-nano pores. Pore diameter varies from 20 to 4000 nm but differs among micro-fossil groups. The widely distributed siliceous micro-fossils, such as radiolarians and sponge spicules, could enhance the brittleness of shales. They may promote the development of natural fractures during diagenesis or artificial fractures during stimulation. When fractures are connected with micro-nano pores in the shale, they could provide effective storage space and improve the overall connectivity. In most of the analyzed shale samples, micro-fossils show positive correlation with high TOC strata. Considering the importance of micro-fossils and their pores in the perspective of hydrocarbon generation, connectivity, accumulation, and production of shale gas, we suggest that micro-fossil pores should be included in the classification of pore systems. Highlights: Micro-fossil pores in gas shales were characterized for the first time. Primary micro-fossils of the Wufeng-Lungmachi Shale were identified. The Wufeng-Lungmachi Shale contains numerous biological micro-nano pores. Micro-fossil pores provide storage space and increase connectivity of shales. A modified classification system of pores in shales was proposed.